The Whistleblower Act and Labour Protection Issues - Walczak, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
In the article, the author tries to justify the thesis that the Whistleblower Act should not cover the issue of reporting breaches of labor law. Justifying his position, the author presents the following arguments. First of all, the Directive on the protection of persons who report breaches of EU law does not impose such an obligation on the Member States. This is because it concerns strictly defined provisions that do not include labour law. Secondly, the Directive provides for the possibility of extending its scope to other branches of law, but this is optional. In the author’s opinion, there are already relevant regulations in Poland in this area, which have been presented in detail. Thirdly, the introduction of the whistleblower into labour law may have serious practical consequences in terms of personnel management.